Application of Differentiated Discovery Learning Based on Drawing Traditional Ornamental Varieties in Fine Arts Subjects to Improve Learning Outcomes of Students in Class VII-H - Mas'udah, Nabillah Raihanah; Prasetyo, Abdul Rahman (IJESS International Journal of Education and Social Science, 2025)
This research focuses on applying the Differentiated Discovery Learning model based on drawing traditional decorative varieties in fine art subjects to improve learning outcomes for students. Based on observations on the subject of fine arts, a problem was found in students in grade VII-H at SMP Negeri 02 Batu related to low learning outcomes in drawing materials of traditional ornamental varieties. This model combines a Discovery Learning strategy with a differentiation approach, which tailors the learning strategy to the learners' abilities, interests, and learning styles. The subjects in this study are students of class VII-H SMP Negeri 02 Batu with a total of 30 students. The method used in this study is Classroom Action Research (PTK) with Mc cycles based on Kemmis and McTaggart, which consists of two cycles. Each cycle includes the stages of planning, implementation of actions, observation, and reflection. Data collection procedures were collected through observations, interviews, questionnaires, and documentation. Quantitative and qualitative methods are used for data analysis. The implications of this PTK research show that the application of Differentiated Discovery Learning can improve student learning outcomes. The results showed that with the implementation of Differentiated Discovery Learning, the percentage of pre-action data was obtained by 40%, in the first cycle by 60% and in the second cycle by 90%. Therefore, it can be concluded that the application of Differentiated Discovery Learning can improve the learning outcomes of fine arts students in class VII-H SMP Negeri 02 Batu on traditional decorative drawing materials.